The Lingua Franca Core: A Plausible Option? - Marco Sandro Antonio Ugarte Olea (Asociación Colombiana de Profesores de Ingles, 2019)
One important decision that English language teachers should make is to decide on a pronunciation model. This decision should be based not only on mere preference, but also on technical information. This paper seeks to review the Lingua Franca Core (LFC), a pronunciation model proposed by Jennifer Jenkins (1998, 2000) in an attempt to facilitate communication for L2 speakers. This paper also presents a set of reactions that her proposal has prompted in scholars in the area of teaching English language pronunciation. Such reactions are the manifestation of rejection of the LFC which is based on a number of arguments. First, there is no agreement as to the number of interactions that occur in English in L1 and L2 contexts. Thus, the predominant use of L2 speakers of English is questioned. Secondly, the advantage of the intelligibility of non-native speakers over native speakers in interaction with other non-native speakers is also subjected to scrutiny. Finally, a special focus on implications for the L1-Spanish-speaking learner of English is proposed, as well as for English language teachers who teach pronunciation. For instance, a series of issues which could facilitate the learner's workload is discussed. One the other hand, the implementation of the LFC implies that the amount of work to be done by the teacher would be drastically increased. This necessarily entails a disadvantage in terms of both time and teaching materials to be allocated by the English Language Teaching (ELT) professional.